2021
DOI: 10.1007/s40670-020-01198-3
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Study Strategy Modifications Using Cognitive Load Theory and Dual Processing Theory in the First Year of Medical School

Abstract: Navigating the beginning of medical school can be challenging for students. The new learning environment and the increased volume and complexity of information presented within a short period of time demand more efficient and effective study strategies. We describe the experience and perspective of a first-year medical student, as well as the adjustment of study strategies based on the application of cognitive load theory and dual processing theory. We provide practical approaches that promote intentional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Under such conditions, students may experience increased cognitive load. The corresponding literature suggests that an increase in cognitive load is one of the main problems of medical students, especially in first year [46]. In our study, an increase in intrinsic cognitive load was confirmed with a general mean of 3.02 ± 0.92 (on a scale of 4), also observing a trend of greater load in the first year (3.05 ± 1.03).…”
Section: Learning Management and Efficacy Skills: Cognitive Loadsupporting
confidence: 87%
“…Under such conditions, students may experience increased cognitive load. The corresponding literature suggests that an increase in cognitive load is one of the main problems of medical students, especially in first year [46]. In our study, an increase in intrinsic cognitive load was confirmed with a general mean of 3.02 ± 0.92 (on a scale of 4), also observing a trend of greater load in the first year (3.05 ± 1.03).…”
Section: Learning Management and Efficacy Skills: Cognitive Loadsupporting
confidence: 87%
“…Intrinsic cognitive load is mainly attributed to the complexity and difficulty of learning material [14]. In our study, the same topic was given over the three teaching modalities by the same instructor and was designed to be with the same difficulty and complexity.…”
Section: Discussionmentioning
confidence: 99%
“…While the intrinsic cognitive load is concerned with the inherent difficulty and complexity of the knowledge that needs to be acquired. Germane cognitive load is the remaining cognitive capacity of the working memory that is required to create or modify schemas while consciously processing information [14].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Guided by this framework, YH created two methods to combat the roadblocks above. [7][8][9][10] First is recognition and correction of weak topics via Self-assessment, Identification, and Patching of knowledge gaps (SIP). These are topics in which the learner misses questions or lacks understanding.…”
Section: Introductionmentioning
confidence: 99%